A method for measuring detailed demand for workers' competences - Robert Pater; Jaroslaw Szkola; Marcin Kozak (Kiel Institute for the World Economy (IfW), 2018)
There is an increasing need for analysing demand for skills at labour markets. While most studies aggregate skills in groups or use available proxies for them, the authors analyse companies' demand for individual competences. Such an analysis better reflects reality, because companies usually require from future workers particular competences rather than generally defined groups of skills. However, no method exists to analyse on a large scale which competences are required by employers. At a detailed level, there are hundreds of competences, so this demand cannot be measured in a sample survey. The authors propose a method for a continuous and efficient analysis of demand for new workers' competences. The method is based on gathering internet job offers and analysing them with data mining and text analysis tools. They applied it to analyse transversal competences on a Polish labour market during November 2012- December 2015. The authors used the detailed European Commission classification of transversal competences. They found that within the general groups of competences, companies required only certain ones, especially 'language and communication competences' and neglected others. The companies' requirements were countercyclical, that is, they increased them during recession and decreased them during economic expansion. However, the structure of the demanded competences did not change during the analysed period, suggesting that the structure is relatively stable, at least over the business cycle. The method can be used continuously. Various institutions can analyse and publish up-to-date information on the current demand for competences as well as tendencies in this demand.
http://dx.doi.org/10.7910/DVN/VSUMVJ
Keywords: I20; J63; 330; online data; skill demand; text analysis; vacancy market; worker competence; worker competency